2014
DOI: 10.1589/jpts.26.291
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pilates Mat Exercise on the Balance Ability of Elderly Females

Abstract: [Purpose] The purpose of this study was to examine the effects of Pilates exercise on a mat and balance exercise on an unstable base of support for trunk stability on the balance ability of elderly females. [Subjects and Methods] Forty elderly women aged 65 or older were equally assigned to a Pilates mat exercise (PME) group and an unstable support surface exercise (USSE) group. They conducted exercise three times per week for 12 weeks for 40 minutes each time. In order to examine balance, sway length and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 14 publications
(13 reference statements)
5
72
0
9
Order By: Relevance
“…In terms of the type of study, the majority used experimental models, 5,7,13,15,18,[20][21][22]24,25 with only two randomized clinical trials. 13,24 The other studies were of different types, with one literature review 3 , one systematic review 12 , one pilot study 19 , one longitudinal study, 23 one case study 16, one observational study 17 and an observational prospective cohort study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the type of study, the majority used experimental models, 5,7,13,15,18,[20][21][22]24,25 with only two randomized clinical trials. 13,24 The other studies were of different types, with one literature review 3 , one systematic review 12 , one pilot study 19 , one longitudinal study, 23 one case study 16, one observational study 17 and an observational prospective cohort study.…”
Section: Resultsmentioning
confidence: 99%
“…7,[12][13][14][15][16][17][18][19] This fact can be justified by the balance deficit inherent to aging, which represents a major disabling factor among this population, interfering with functionality and quality of life. The topics described below were stipulated in order to facilitate understanding of the results with respect to all the variables described in the studies analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyun et al (2014) reported significant effects on balance by Pilates exercises and balance exercises on unstable surfaces in old women. Estimates however showed that Pilates exercises are safer and simpler to improve balance skills, especially dynamic balance, in this group [13]. Considering the higher rate of imbalance and falls in old patients with PD rather than healthy ones, this type of exercises can therefore play a key role in improving motor functions and balance in these patients [14].…”
Section: Introductionmentioning
confidence: 93%
“…Newell et al (2012), who studied the effects of Pilates exercises on balance and walking in older adults, concluded that short-term Pilates exercises can significantly improve variables associated with walking and balance and therefore reduce the risk of falls in this group [12]. Hyun et al (2014) reported significant effects on balance by Pilates exercises and balance exercises on unstable surfaces in old women. Estimates however showed that Pilates exercises are safer and simpler to improve balance skills, especially dynamic balance, in this group [13].…”
Section: Introductionmentioning
confidence: 99%